(untitled) (Architecture Image Studies, 2026)
The number of natural disasters is increasing day by day due to climate change and pop-ulation growth. Disasters increase loss of life and property when city plans are prepared without sufficient consideration and land use decisions are made. In 2010, 2014 and 2021, floods in Antalya caused significant material losses in many districts. In recent years, in-creasing floods in the city centre of Manavgat, Antalya, have caused economic losses and expanded their area of impact. In this context, the aim of this study is to analyse the rela-tionship between land use and floods in Manavgat using the Analytical Hierarchy Pro-cess (AHP) and Geographic Information System (GIS) techniques, thereby offering rec-ommendations for risk reduction. The study covers the identification of areas at risk of flooding and the development of settlement proposals for these areas. An analysis map has been prepared within this scope. Risk increases in low-altitude agricultural areas and urban areas with high rainfall, while it decreases in areas with low rainfall, high altitude and forested areas. Therefore, land use should be planned according to scientific and geo-graphical data, construction should be restricted in hazardous areas, permeable surfaces should be increased, and the destruction of forested areas should be prevented